Glycated haemoglobin A1c (HbA1c) for detection of diabetes mellitus and impaired fasting glucose in Malawi: a diagnostic accuracy study. Issue 5 (5th May 2018) - Rathod, Sujit D; Crampin, Amelia C; Musicha, Crispin; Kayuni, Ndoliwe; Banda, Louis; Saul, Jacqueline; McLean, Estelle; Branson, Keith; Jaffar, Shabbar; Nyirenda, Moffat J
Abstract : Objectives: To examine the accuracy of glycated haemoglobin A1c (HbA1c ) in detecting type 2 diabetes and impaired fasting glucose among adults living in Malawi. Design: A diagnostic validation study of HbA1c . Fasting plasma glucose (FPG) ≥7.0 mmol/L was the reference standard for type 2 diabetes, and FPG between 6.1 and 6.9 mmol/L as impaired fasting glucose. Participants: 3645 adults (of whom 63% were women) recruited from two demographic surveillance study sites in urban and rural Malawi. This analysis excluded those who had a previous diagnosis of diabetes or had history of taking diabetes medication. Results: HbA1c demonstrated excellent validity to detect FPG-defined diabetes, with an area under the receiver operating characteristic (AUROC) curve of 0.92 (95% CI 0.90 to 0.94). At HbA1c ≥6.5% (140 mg/dL), sensitivity was 78.7% and specificity was 94.0%. Subgroup AUROCs ranged from 0.86 for participants with anaemia to 0.94 for participants in urban Malawi. There were clinical and metabolic differences between participants with true diabetes versus false positives when HbA1c was ≥6.5% (140 mg/dL). Conclusions: The findings from this study provide justification to use HbA1c to detect type 2 diabetes. As HbA1c testing is substantially less burdensome to patients than either FPG testing or oral glucose tolerance testing, it represents a useful option for expanding access to diabetes care in sub-Saharan Africa.